TI_GERICHTE 52.2020.364 vom 24. Juni 2020 , Commessa pubblica. Aggiudicazione di un mandato di progettazione. Conformità offerta. Referenze - TI Tribunale d'appello (2020)
Commessa pubblica. Aggiudicazione di un mandato di progettazione. Conformità offerta. Referenze